Adaptive control for a class of state-constrained high-order switched nonlinear systems with unstable subsystems. (May 2019) - Sun, Yaowei; Zhao, Jun; Dimirovski, Georgi M.
Abstract: In this paper, the adaptive stabilization issue for a class of state-constrained high-order switched nonlinear systems is concerned, where all subsystems are allowed to be unstabilizable. A novel adaptive control scheme is established by exploiting the effective coupling of the technique of adding a power integrator and the method of multiple barrier Lyapunov functions. Explicitly, a group of adaptive controllers and a proper switching law are designed to asymptotically regulate the states of the resulting closed-loop system in a domain and meanwhile guarantee that the violation of the constraints does not happen. Contrary to a common update law constructed for all subsystems in the literature, different update laws for individual subsystems are designed separately to reduce the conservativeness. Moreover, at the switching instants, the connection of two adjacent barrier Lyapunov functions is not be required and even a certain amount of grow is also allowed. Finally, a simulation example is performed to further illustrate the effectiveness of the provided control strategy.